PLANNING DESIGN OF SPILLWAY SURUMANA DAM IN DONGGALA DISTRIC, CENTRAL SULAWESI - NURFAJRIN ASHARI - Nim: 15813037 , RENGGANIS
Surumana Dam which is located in Donggala District, Central Sulawesi have 199.5 Km2 in watershed area. The dam serve as a provider of raw water, irrigation, and flood control. One of the important components of the Surumana Dam is the Spillway. The type of the spillway in Surumana Dam is Side Spillway with the crest type is ogee and total length for this spillway is 349 Km from the side channel up to stilling basin. Design of this spillway is using Q1000 and controlled using QPMF which means this spillway must be able to drain the water when conditions Q1000 and also QPMF. For the frequency analysis is using the GumbleÃ‚Â’s Method and for the flood discharge is design using SCS syntetic technic unit hidrograf. Routing for this spillway is calculated using HEC-HMS 4.0 and the flow modelling is perform by HEC-RAS 5.0.3. The crest elevation of the spillway is at +89 m and the elevation of stilling basin is at +40 m, where the top crest of the main dam is at +95 m. The calculation of stability is check against the overturning, sliding, and eccentricity in the condition of MAN and MAB.